Music industry and the internet : the case study of soundbuzz - Fam, Li Li (2008)
The music industry has been going through a dramatic transformation over the last few years due to technological developments that have heralded a new era in music distribution and usage. Digital delivery is fast becoming dominant for providing music content in major markets. This has led to the emergence of numerous online entities vying for a share of online and the mobile music business. This study specifically discusses Soundbuzz, the most established digital music provider in the Asia-Pacific region. It discusses how Soundbuzz evolved through the years and how it gained raction from a startup in the B2B space to a major music portal in the B2C space. Factors critical to its success are highlighted and lessons for others in the music space and broadly in the online arena are detailed from the experiences of this innovator in a very challenging and disruptive industry.